Three new chlorophenolic glucosides from Curculigo orchioides Gaertn. (August 2018) - Wang, Zhen-Hui; Gong, Xue-Yun; Zhou, De-Jun; Xu, Peng-Fei; Huang, Mei; Zhang, Qing-Ling; Meng, Yue-Li; Niu, Chao; Zhang, Yan-Ru
Graphical abstract: Highlights: Three new chlorophenolic glucosides were isolated from the dried rhizomes of Curculigo orchioides Gaertn. Antiosteoporotic activity were evaluated for the isolated chlorophenolic glucosides. Compounds 1, 2 and 3 showed moderate antiosteoporotic activity with the proliferation rate of 11.2–15.9%. Abstract: Three new chlorophenolic glucosides, Curculigine M (1), Curculigine N (2) and Curculigine O (3) were isolated from the dried rhizomes of Curculigo orchioides Gaertn. Their structures were identified by means of spectroscopic methods such as 1D, 2D NMR and MS. These chlorophenolic glycosides were evaluated for effect on osteoblast proliferation against MC3T3-E1 cell line by using MTT assays. Compounds 1, 2 and 3 showed moderate effect on osteoblast proliferation with the proliferation rate of 11.2–15.9%.